Bird Diversity in Rambut Island Wildlife Reverse Seribu Islands - Nurfadila, Imelda; Muthiah, Anis (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2021)
Indonesia is one of the top priority countries in efforts to preserve biodiversity because it has the largest biodiversity in the world. Rambut Island Wildlife Reserve is a nature reserve area with a wetland ecosystem type. This study aims to analyze the diversity of bird species in the Pulau Rambut Wildlife Reserve area. This research was conducted in May-July 2021. The method used for this study was a literature study. The diversity of bird species on Rambut Island, Kepulauan Seribu is quite high, as indicated by 24 species of birds. The existence of the activities of the people of Untung Jawa Island is thought to have an influence on the diversity of bird species found on Rambut Island, Kepulauan Seribu. Therefore, the role of BTNLKpS managers is needed to maintain the preservation and diversity of bird species found on Rambut Island, Kepulauan Seribu.